Combination of BMP2 and MSCs significantly increases bone formation in the rat arterio-venous loop model - Bührer, Gregor; Balzer, Amelie; Arnold, Isabel; Beier, Justus; Koerner, Carolin; Bleiziffer, Oliver Anton; Brandl, Andreas; Weis, Christian; Horch, Raymund; Kneser, Ulrich; Arkudas, Andreas (Tissue engineering, 2015)
Introduction: In this study the induction of bone formation in an axially vascularized bone matrix using mesenchymal stem cells (MSCs) and application of bone morphogenetic protein 2 (BMP2) was analyzed in the arteriovenous loop (AVL) model.Materials and Methods: An AVL was created in the medial thigh of 42 rats and placed in a porous titanium chamber filled with a particulated porous hydroxyapatite and beta-tricalcium phosphate matrix and fibrin. In group A the fibrin was loaded with 5×106 DiI-stained fibrin gel-immobilized primary MSCs from syngenic Lewis rats, in group B the matrix was loaded with 60 μg/mL BMP2 and in group C both, BMP2 and MSCs were applied at implantation time point. After 6 and 12 weeks, specimens were investigated by means of histological, morphometrical, and micro-computed tomography analysis.Results: After implantation of an AVL a dense vascular network was visible in all groups. In group A, newly generated bone islands were detected in the periphery of the main vascular axis. Using BMP2 alone (group B), small islands of newly formed bone were visible evenly distributed in all parts of the constructs. In group C nearly the whole matrix was interspersed with bone formations. In all groups there was an increase of bone formation between the 6 and 12 weeks explantation time points.Conclusions: This study demonstrates for the first time the successful generation of axially vascularized bone substitutes using MSCs and BMP2 in the AVL rat model using a one step procedure. Using the combination of BMP2 and MSCs there was a significant increase of bone formations detectable compared to the BMP2 or MSCs alone groups.